Needs Analysis of a Multimodal E-Module for Critical Reading Using the Critical Digital Literacy Approach for University Students in West Java - Veni Nurpadillah; Fathur Rokhman; Rahayu Pristiwati (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2026)
This study aims to analyze students' needs for the development of a multimodal e-module based on critical digital literacy to enhance critical reading skills in digital news texts. The study is grounded in the challenges of digital literacy in the Society 5.0 era, where students are exposed to various forms of digital information but lack the ability to filter, evaluate, and interpret information critically. Using a Research and Development (R&D) approach and the ADDIE model, this study focuses on the needs analysis phase as a foundation for instructional material development. Data were collected through classroom observations, lecturer interviews, and a questionnaire administered to 196 students from five universities in West Jawa. Findings indicate that most students frequently read digital news via social media but are also often exposed to biased or false information. Students report difficulty distinguishing between facts and opinions and express a strong need for skills in interpreting symbols, images, and hidden meanings in multimodal texts. The majority of respondents show interest and feel supported by interactive e-modules that present material using text, video, and animation. These findings emphasize the urgent need for the development of a multimodal e-module based on Critical Digital Literacy as a relevant and contextual learning strategy. The proposed module is expected to equip students not only with critical reading abilities but also with ethical and reflective awareness to navigate the complex digital information ecosystem.